Implications of physical activity practice on cardiometabolic indicators in the post-menopause period: A review of the literature (Research, Society and Development, 2023)
The objective of this research is to evaluate the effects of physical exercise on the cardiovascular and metabolic parameters of postmenopausal women. 10 studies published between 2014 and 2023 were selected in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS); Spanish Bibliographic Index of Health Sciences (IBECS); Specialized Bibliographic Database in the Nursing Area (BDENF); Medical Literature Analysis and Retrieval System Online (Medline). The studies were divided into three categories, according to the main results found: Improvement in lipid metabolism, reduction in abdominal circumference and weight loss; Reduction of systolic blood pressure, prevention of the development of arterial hypertension and reduction of the release of sympathomimetic hormones; Elevation of antioxidant mediators and reversal of oxidative stress. Studies in the three categories demonstrated beneficial effects of physical exercise on the cardiovascular and metabolic parameters of postmenopausal women. The results suggest that regular physical exercise is an effective strategy for improving the cardiovascular and metabolic health of postmenopausal women.